2019
DOI: 10.1002/fsn3.1144
|View full text |Cite
|
Sign up to set email alerts
|

Thin‐layer drying of parchment Arabica coffee by controlling temperature and relative humidity

Abstract: This paper presents thin‐layer drying of parchment coffee (Coffea arabica). Thin‐layer drying of parchment coffee was conducted under controlled temperatures (50°C, 60°C, and 70°C) and relative humidities (10%–30%). The temperature of the drying air was important for drying at a high temperature, which results in the rapid removal of moisture and reduced time for drying. Nine thin‐layer drying models (Newton, Page, Henderson and Pabis, logarithmic, two‐term, modified Henderson and Pabis, two‐term exponential, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 27 publications
5
23
0
7
Order By: Relevance
“…The effective diffusivity values in this experiment are found to be within a range of 10 − 11 to 10 − 9 m 2 /s, which is generally considered the acceptable range for most agricultural and food products (Aviara et al 2016). Another study, performed by Phitakwinai et al (2019), reports that the effective diffusivity values of coffee beans dried at 50°C-70°C ranged from 7.7544.10 − 10 to 1.4525.10 − 9 . It can be seen that higher temperatured will increase the effective diffusivity value (Alara et al 2017).…”
Section: Mathematical Modelingsupporting
confidence: 55%
See 2 more Smart Citations
“…The effective diffusivity values in this experiment are found to be within a range of 10 − 11 to 10 − 9 m 2 /s, which is generally considered the acceptable range for most agricultural and food products (Aviara et al 2016). Another study, performed by Phitakwinai et al (2019), reports that the effective diffusivity values of coffee beans dried at 50°C-70°C ranged from 7.7544.10 − 10 to 1.4525.10 − 9 . It can be seen that higher temperatured will increase the effective diffusivity value (Alara et al 2017).…”
Section: Mathematical Modelingsupporting
confidence: 55%
“…Therefore, Page model is the most suitable model for describing the drying behavior of coffee beans, followed by the Modified Page model and the Henderson and Pabis model. However, other research about thin-layer drying of coffee report that Midilli et al model is the best model (Siqueira et al 2016;Deeto et al 2018), while Phitakwinai et al (2019) found that Modified Midilli et al model is the best model, although the Page model also described the coffee beans' drying behavior. These differences in best model selection may be caused by different drying methods and conditions (Onwude et al 2016).…”
Section: Mathematical Modelingmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, since the relative humidity of the drying air decreases at high temperatures, moisture holding capacity increases. Phitakwinai, Thepa, and Nilnont (2019) also reported that drying at a low relative humidity decreases the vapor pressure causing the water inside the product to evaporate rapidly in large quantities. This case increases the rate of moisture diffusion, which is important in the mass transfer between the sample and the air, thereby the water diffusion rate increases T A B L E 3 Non-linear regression analysis results of semi-empirical models for freeze drying of turkey breast meat (Submitted, 2007).…”
Section: Effective Diffusion Coefficient and Estimation Of Activatimentioning
confidence: 99%
“…Selain itu upaya peningkatan mutu produk kopi masih menjadi hal penting, terutama yang berkaitan dengan pengaruh suhu dan waktu pada saat penyangraian (Mendes et al, 2001;Tadesse et al, 2015;Aliah et al, 2015;Shan et al, 2016). Pada sisi yang lain, juga penting untuk memperhatikan aspek lain yang berpengaruh pada mutu, misalnya fermentasi (Kwak et al, 2018; Haile dan Kang, 2019), aspek penyimpanan pada kopi (Kruemel et al, 2013), pengeringan biji kopi (Ghosh dan Venkatachalapathy, 2014; Phitakwinai et al, 2019).…”
Section: Sampel Dan Metode Analisisunclassified